Oligodeoxynucleotide inhibition of Toll‐like receptors 3, 7, 8, and 9 suppresses cytokine production in a human rheumatoid arthritis model. Issue 3 (16th December 2015) - Sacre, Sandra; Lo, Alexandra; Gregory, Bernard; Stephens, Matthew; Chamberlain, Giselle; Stott, Philip; Brennan, Fionula
Abstract : The inhibitory oligodeoxynucleotide ODN1411 was found to suppress activation of TLRs 3, 7, 8, and 9 in primary human cells, possibly through a direct interaction with these receptors. ODN1411 also significantly decreased spontaneous cytokine production from human rheumatoid synovial membrane tissue in culture. Abstract : Toll‐like receptors (TLRs) are innate immune receptors that respond to both exogenous and endogenous stimuli and are suggested to contribute to the perpetuation of chronic inflammation associated with rheumatoid arthritis (RA). In particular, the endosomal TLRs 3, 7, 8, and 9 have more recently been postulated to be of importance in RA pathogenesis. In this study, pan inhibition of the endosomal TLRs by a phosphorothioate‐modified inhibitory oligodeoxynucleotide (ODN) is demonstrated in primary human B cells, macrophages, and RA fibroblasts. Inhibition of TLR8 was of particular interest as TLR8 has been associated with RA pathogenesis in both human and murine arthritis models. ODN1411 competitively inhibited TLR8 signaling and was observed to directly bind to a purified TLR8 ectodomain, suggesting inhibition was through a direct interaction with the receptor. Addition of ODN1411 to human RA synovial membrane cultures significantly inhibited spontaneous cytokine production from these cultures, suggesting a potential role for one or more of the endosomal TLRs in inflammatory cytokine production in RA and the potential for inhibitory ODNs as novel therapies.